Prenatal consultation by nurses from the perspective of pregnant women: an integrative review (Research, Society and Development, 2022)
Objective: This study aimed to describe the vision of pregnant women about the nurse's prenatal consultation. Methodology: This is an integrative literature review conducted with 10 articles published between 2018 and 2022 and indexed in the Virtual Health Library (BVS), CAPES Periodicals Portal and Scientific Electronic Library Online (SciELO). During the search 300 articles were found with the use of predefined descriptors and the Boolean Operators AND and OR, being excluded literature reviews, case reports, publications not available in Portuguese and that did not converge with the study proposal. Results: In the selected studies, the prenatal care provided by the nurse was mostly perceived as satisfactory, with the reception and good communication being highlighted. However, factors associated with dissatisfaction were found, such as doubts about the technical capacity of the professional to conduct consultations and long waiting times. Conclusion: Therefore, it was essential to know the perception of patients and thus identify flaws and qualities of care, providing subsidies for professional improvement.